Oncolytic virus therapy in the elderly: immune frailty, challenges, and perspectives - Wang, Jia-Wen; Liu, Jia-Hui; Liu, Yue-Lin; Xu, Wen-Zheng; Zhang, Zi-Bo (Frontiers in Immunology, 2025)
With global aging accelerating, cancer incidence among older adults is rapidly increasing. Individuals aged ≥65 years now represent 64% of new cancer cases and 71.3% of cancer-related deaths worldwide. This population exhibits a distinct immune imbalance—driven by tumor-induced immunosuppression, immunosenescence, and inflammaging—which contributes to poor tolerance of standard therapies and suboptimal outcomes with PD-1/PD-L1 inhibitors.As an emerging immunotherapeutic strategy, oncolytic viruses (OVs) selectively infect tumor cells, induce immunogenic cell death (ICD), and activate the cGAS–STING pathway. Although clinical data in elderly patients with esophageal, lung, or pancreatic cancer are scarce, promising outcomes have been reported in melanoma/sarcoma subgroups, including objective response rates of 26.4–32.9% and a median duration of response of 33.7 months, highlighting the potent antitumor potential of OVs.However, age-related immunological vulnerability—manifesting across different frailty stages as reflected by G8 scoring—may predispose elderly patients to immune overload, cytokine storm, and impaired tolerance, while this group remains underrepresented in OV trials. Systematic studies in this context are lacking. This review highlights the immunological characteristics of aging, emphasizes the importance of addressing immunological vulnerability across different age stages (G8 scoring), and outlines emerging challenges and future directions for OV-based therapies tailored to frail elderly populations.